A chemosensitive based ammonia gas sensor with PANI/PEO- ZnO nanofiber composites sensing layer - AKAY, ÖZGE; YÜCE, HÜSEYİN (My University, 2023)
Purpose: The purpose of this study is to investigate the ammonia sensing performance of polyaniline/polyethylene oxide (PANI/PEO) and polyaniline/polyethylene oxide/zinc oxide (PANI/PEO-ZnO) composite nanofibers at room temperature. Design/methodology/approach: Gas sensor structures were fabricated using micro-fabrication techniques. First, onto the SiO2 wafer, gold electrodes were fabricated via thermal evaporation. PANI/PEO nanofibers were produced by the electrospinning method and the ZnO layer was deposited by RF magnetron sputtering on the electrospun nanofibers as a sensing layer. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were performed for characterization analysis of nanofibers. After all, gas sensing analysis of PANI/PEO and PANI/PEO/ZnO nanofibers was performed using an experimental setup at room temperature conditions. Findings: FTIR analysis confirms the presence of functional groups of PANI, PEO and ZnO in nanofiber structure. SEM images demonstrate beads-free, thinner and smooth nanofibers with ZnO contribution to electrospun PANI/PEO nanofibers. Moreover, according to the gas sensing results, the PANI/PEO nanofibers exhibit 115 and 457 s response time and recovery time, respectively. However, the PANI/PEO/ZnO nanofibers exhibit 245 and 153 s response time and recovery time, respectively. Originality/value: In this study, ZnO was deposited via RF magnetron sputtering techniques on PANI/PEO nanofibers as a different approach instead of in situ polymerization, to investigate and enhance the sensor response and recovery time of the PANI/PEO/ZnO and PANI/PEO composite nanofibers to ammonia. These results indicated that ZnO can enhance the sensing properties of conductive polymer based resistive sensors.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Atom ve Molekül Fiziği; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Atomic and Molecular Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; KİMYA, FİZİKSEL; FİZİK, YOĞUN MADDE; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; PHYSICS; ENGINEERING, ELECTRICAL & ELECTRONIC; CHEMISTRY, PHYSICAL; PHYSICS, CONDENSED MATTER; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Yoğun Madde Fiziği; Yüzeyler, Kaplamalar ve Filmler; Elektrik ve Elektronik Mühendisliği; Electronic, Optical and Magnetic Materials; Physical Sciences; Atomic and Molecular Physics, and Optics; Condensed Matter Physics; Surfaces, Coatings and Films; Electrical and Electronic Engineering; Composites; Gas sensor; Nanofibers; PANI; Polymer